(untitled) (Pakistan Journal of Science, 2023)
Strangles is the most common infectious and contagious disease of equines that affects upper respiratory tract. It is prevalent among the horses in sub-continent from pre partitioned times, an effective study to isolate locally prevalent strains in the area and study of factors affecting their consequent growth is essential. For the said purpose, twenty nasal swab samples were collected, ten from clinically sick and ten from apparently healthy horses with the history of disease. Isolated strains were undergone identification through biochemical and lancefield testing. Maximum in-vitro growth of Streptococcus equi (S. equi) is a critical factor for its cost effective bioceutics production. Effect of different factors like composition of medium such as (Tryptic Soy Broth (TSB), Nutrient Broth, Brain Heart Infusion broth (BHI), Reinforced Clostridial Medium (RCM) and Peptone Broth, pH (5, 7, 9), gas (oxygen availability, 5% CO2, aeration), horse serum (2%, 5%, 10%) and temperature (35°C, 37°C, 39°C) on growth of S. equi was therefore carried out. Growth was expressed in form of Colony Forming Units (CFU) which was converted into log values followed by statistical analysis. TSB among media, pH 7, CO2 5% gas, horse serum 5% and incubation temperature 37°C showed optimum growth of S. equi.